Pengaruh Sumber DAya Manusia dan Pemanfaatan Teknologi Informasi Akuntansi Terhadap Kinerja Pelaporan Keuangan Tahun 2010-2013 Pada Pemerintah Kota Surakarta - Budiarti, Zega; Nurlaela, Siti; Masitoh, Endang (STIE Surakarta, 2015)
This study aimed to examine the effect of human resources and technology utilization of accounting information on the performance of financial reporting Surakarta municipal government. Samples were employees / staff DPPKA in the Surakarta municipal government agencies. Data were collected by taking 50 respondents from the area of the budget, treasury field, the field of assets and accounting and secretariat of the local government areas of the city of Surakarta. Methods of data collection was done by using purposive sampling judgment through the survey. Results of research in the formulation of hypothesis H1 indicates that human resources are not significantly positive effect on the performance of financial reporting. While the results of a second study in the formulation of hypothesis H2 suggests that the existence of significant influence positively the use of information technology accounting significant positive effect on the performance of financial reporting. Simultaneous trials and research results show that the existence of significant positive effect between human resources and technology utilization of accounting information on the performance of financial reporting.